(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, we explain the concept of financial translation and the types of financial documents. We also focus on the challenges of financial translation and the importance of hiring an expert. Finally, we answer some frequently asked questions on this topic.